British Cancer Research Meeting, 30 June-3 July 2002, Glasgow - Parkes, Alicia T (BioMed Central, 2002)
The 2002 British Cancer Research Meeting was held from 30th June to 3rd July in Glasgow, UK. The meeting was structured to include educational workshops, plenary lectures, symposia, and poster sessions, which brought together scientists and clinicians. Presentations ranged from the impact that modifications to basic chromatin structure can have on diagnosis and targeted gene therapy, to the outcome of novel therapeutics through clinical trials. The emphasis was clear: patient survival is the main priority and treatment of organ-specific cancer must inevitably be replaced by individualised tumour-specific therapy.